Role of interleukin-6 in inhibiting hepatic autophagy markers in exercised mice. (June 2020) - Pinto, Ana P.; da Rocha, Alisson L.; Cabrera, Elisa M.B.; Marafon, Bruno B.; Kohama, Eike B.; Rovina, Rafael L.; Simabuco, Fernando M.; Bueno Junior, Carlos R.; de Moura, Leandro P.; Pauli, José R.; Cintra, Dennys E.; Ropelle, Eduardo R.; et al.
Abstract: Background: Based on the crosstalk of inflammation with apoptosis, autophagy, and endoplasmic reticulum (ER) stress, the main objective of this study was to explore the role of interleukin-6 (IL-6) on genes and proteins related to these phenomena in the livers of mice submitted to acute exhaustive exercise. Methods: Reverse transcription-quantitative polymerase chain reaction and immunoblotting technique were used to evaluate the livers of wild-type (WT) and IL-6 knockout (KO) mice at baseline (BL) and 3 h after the acute exhaustive physical exercise (EE). Results: Compared to the WT at baseline, the IL-6 KO had lower exhaustion velocity, mRNA levels of Mtor, Ulk1, Map1lc3b, and Mapk14, and protein contents of ATG5 and p-p70S6K/p70S6K . For the WT group, the EE decreased glycemia, mRNA levels of Casp3, Mtor, Ulk1, Foxo1a, Mapk14, and Ppargc1a, and protein contents of ATG5 and p-p70S6K/p70S6K, but increased mRNA levels of Sqstm1 . For the IL-6 KO group, the EE decreased glycemia, mRNA levels of Casp3 and Foxo1a, and protein contents of pAkt/Akt and Mature/Pro IL-1beta, but increased mRNA levels of Sqstm1, and protein contents of p-AMPK/AMPK. Conclusion: The inhibition of the hepatic autophagy markers induced by the acute EE was attenuated in IL-6 KO mice, highlighting a new function of this cytokine.